(untitled) (The Review of Diabetic Studies, 2025)
Background: Patient safety culture is a critical determinant of healthcare quality, influencing error reporting, teamwork, communication, and overall clinical outcomes. Leadership style is widely recognized as a key driver of safety culture, shaping staff behaviors, organizational learning, and adherence to safety protocols. However, existing evidence varies across settings and leadership models, necessitating a comprehensive synthesis. Objective: This systematic review aims to examine the impact of different leadership styles—such as transformational, transactional, laissez-faire, authentic, and servant leadership—on patient safety culture across diverse healthcare environments. Methods: A systematic search was conducted across major databases including PubMed, Scopus, Web of Science, CINAHL, and Cochrane Library for studies published from 2010 to 2025. Eligible studies included quantitative, qualitative, and mixed-methods designs that evaluated both leadership style and patient safety culture using validated tools. Data extraction and quality appraisal were performed independently by two reviewers, and findings were synthesized narratively due to methodological heterogeneity. Results: Thirty-four studies met the inclusion criteria. Transformational and authentic leadership were consistently associated with improved safety culture indicators such as communication openness, teamwork, safety climate, and incident reporting. Transactional leadership showed mixed effects, often enhancing compliance with safety procedures but offering limited influence on broader cultural dimensions. Laissez-faire leadership was linked to poorer safety outcomes, including low staff engagement and reduced error reporting. Servant leadership demonstrated positive associations with psychological safety and team cohesion, though evidence remains limited. Across studies, leadership visibility, feedback mechanisms, and support for staff learning emerged as important mediators. Conclusion: Leadership style plays a significant and measurable role in shaping patient safety culture. Transformational and authentic leadership approaches appear most effective in fostering a positive safety environment, while laissez-faire styles undermine safety efforts. Healthcare organizations should invest in leadership development programs that emphasize communication, engagement, and supportive behaviors to strengthen patient safety culture and enhance clinical outcomes.